2017
DOI: 10.13044/j.sdewes.d5.0177
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic Assessment of Integrated Hydrothermal Liquefaction and Combined Heat and Power Production from Lignocellulose Residues

Abstract: Waste biomass as a mean for global carbon dioxide emissions mitigation remains under-utilized. This is mainly due to the low calorific value of virgin feedstock, characterized generally with high moisture content. Aqueous processing, namely hydrothermal liquefaction in subcritical water conditions, has been demonstrated experimentally to thermally densify solid lignocellulose into liquid fuels without the pre-requisite and energy consuming drying step. This study presents a techno-economic evaluation of an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The solids CHP boiler is modelled similar to a bubbling fluidized-bed design proposed in [ 32,59 ]. Process heat demand is given precedence in utility network design.…”
Section: Liquid Carriers: Renewable Fuels Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…The solids CHP boiler is modelled similar to a bubbling fluidized-bed design proposed in [ 32,59 ]. Process heat demand is given precedence in utility network design.…”
Section: Liquid Carriers: Renewable Fuels Productionmentioning
confidence: 99%
“…As-penPlus® contains libraries of industrially relevant unit operation blocks that calculate existing chemistry and phase equilibria based on extensive list of thermodynamic routines available in the literature, and compound databases available from the National Institute of Standards and Technology (NIST) Standard Reference Data Program (SRDP) [ 52 ]. Other process modelling tools such as CHEMCAD [ 64 ] and Belsim SA [ 28 ] have been reported, however Aspen Plus® remains the most extensively applied tool in the field [ 37,59,[65][66][67][68][69] ].…”
Section: Aspenplus® Process Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the decrease of specific adsorption with higher hydrothermal temperature could not be conclusive in this study. Nakason et al [13] reported the optimal condition production of hydrochar from corncob as solid fuel which was determined at 200 oC, 3 hour of residence time and biomass to water ratio of 1:5 with maximum energy yield of 68.74%. Magdeldin et al [14] presented the techno-economic performance indicators of integrated hydrothermal liquefaction which densify forest residue lignocellulosic into liquid fuels and combined heat and power production.…”
Section: Figure 1 Hydrothermal Technology Classificationmentioning
confidence: 99%